Development of Quantitative Weathering Indicators in Proximal Alluvial Sediments to Assess Glacial Activity in the Rock Record - Madden, Megan Elwood; Soreghan, Gerilyn (IEDA: US Antarctic Program Data Center, 2011)
Abstract: The proposed research seeks to test the hypothesis that chemical and physical weathering in proximal alluvial systems will show systematic and measurable variations between glacial and nonglacial systems. To accomplish this, the investigation will attempt to quantify the natural variation of chemical and physical weathering in granitoid-sourced proximal alluvial sediments in end-member glacial and nonglacial systems, when other, 'non-climatic' factors (e.g. provenance, drainage basin area and relief, sample grain size, sediment facies) are controlled. If chemical weathering in the proposed hot-humid, hot-arid, hot semi-arid nonglacial systems and the cool-wet, cold semi-arid, and cold-arid glacial systems show systematic variations, then chemical indices may be used to help differentiate paleoclimatic conditions. Continued reliance on students provides a broader impact of this proposed research and firmly grounds this effort in its educational mission.